2019
DOI: 10.1177/1468017319861500
|View full text |Cite
|
Sign up to set email alerts
|

Resisting gentrification: The theoretical and practice contributions of social work

Abstract: Summary Gentrification is changing the landscape of many cities worldwide, exacerbating economic and racial inequality. Despite its relevance to social work, the field has been conspicuously absent from scholarship related to gentrification. This paper introduces the dominant view of gentrification (a political economic lens), highlighting its contributions and vulnerabilities, then introduces four case studies that illuminate the distinct contributions of social work to broaden the ways in which gentrificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 19 publications
0
24
0
3
Order By: Relevance
“…Further, Anguelovski (2016) proposed that a third wave of environmental justice organizing has emerged to address issues related to self‐determination, the defense of place and culture, and resistance to environmental gentrification. For example, in Chicago’s predominately Mexican‐American Little Village neighborhood, environmental justice organizers mobilize for the right to place in response to concerns about environmental gentrification as well as xenophobia and anti‐immigrant practices (Kern & Kovesi, 2018; Thurber et al, 2019). Anguelovski (2016) suggested that the first and second waves of environmental justice organizing were grounded in an assumption that residents, particularly those who are poor or people of color, cannot move away from contaminated and divested neighborhoods; thus, community organizations worked to improve the quality of those places.…”
Section: Environmental Justice Organizing and Social Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Anguelovski (2016) proposed that a third wave of environmental justice organizing has emerged to address issues related to self‐determination, the defense of place and culture, and resistance to environmental gentrification. For example, in Chicago’s predominately Mexican‐American Little Village neighborhood, environmental justice organizers mobilize for the right to place in response to concerns about environmental gentrification as well as xenophobia and anti‐immigrant practices (Kern & Kovesi, 2018; Thurber et al, 2019). Anguelovski (2016) suggested that the first and second waves of environmental justice organizing were grounded in an assumption that residents, particularly those who are poor or people of color, cannot move away from contaminated and divested neighborhoods; thus, community organizations worked to improve the quality of those places.…”
Section: Environmental Justice Organizing and Social Workmentioning
confidence: 99%
“…How do they manage tensions between fighting for neighborhood environmental improvements and indirectly attracting wealthier and, often, whiter newcomers? These questions matter because although gentrification is driven by global political, economic, and social forces, its impacts − and opportunities for contestation and resistance − frequently manifest at the local level (Lees, Slater, & Wyly, 2013; Thurber, Krings, Martinez, & Ohmer, 2019).…”
mentioning
confidence: 99%
“…Bien que les effets de la gentrification fassent partie de la pratique quotidienne du travail social dans les quartiers comme Sainte-Rita, la littérature sur le sujet reste encore peu développée, si on exclut les champs du logement (Thurber et al, 2019) ou du contexte scolaire. La contribution de cet article est de documenter le rapport des mères à la mixité sociale en regardant leur circuit au-delà de l'enceinte scolaire.…”
Section: Mixer Le Social ?unclassified
“…(Ball, Bowe et Gewirtz, 2004). Toutefois, comme le soulignent Thurber et al (2019), peu de recherches se sont intéressées à l'influence de la gentrification sur l'intervention ou le travail social de proximité. Cet article propose de contribuer à répondre à ce manque en analysant de quelle manière la mixité sociale est mise en oeuvre dans les services publics et communautaires 1 destinés à l'éducation à la petite enfance et au soutien à la parentalité.…”
unclassified
See 1 more Smart Citation